Sixty years of fetal psychism. The childhood as a portal - Darré, Silvana (2018)
Starting from the ideas formulated by E. Haeckel in the 19th century about ontogeny and phylogeny, some examples of the production oftheories in the psi field are reviewed. The possibility of studying the history of the human species from the evolutionary history of an individual turned out to be a powerful and inspiring idea. In the article special emphasis is placed on the theory proposed by Arnaldo Rascovsky in the late fifties of the last century and some background is reviewed, such as Otto Rank´s ideas exposed in the Birth Trauma and Lloyd DeMause’s psychohistory. Childhood and the theoretical constructions about the psychism of the prenatal stages of doubtful existence, constitute an opportunity to establish connections between the developments of the psi field, the scientific discourse and marginal thinking.